Comparision of the BAX® System with an in-house MSRV method for the detection of Salmonella in chicken carcasses and pork meat - Franchin,Paulo R. (2006)
A study was performed to compare the analytical procedure of the BAX® System for Salmonella PCR assay with the Modified Semi-Solid Rappaport-Vassiliadis (MSRV) method, for the detection of Salmonella in naturally contaminated chicken carcass samples (n = 762) and raw pork meat (n = 566). The chicken carcasses samples were collected during slaughtering after defeathering or immediately after evisceration and the raw pork meat collected from the deboned head of recently slaughtered pigs and others deboned raw fresh pork meat. The BAX® System detected 134 Salmonella-positive samples in chicken carcasses and 145 samples in pork meat, while the MSRV method isolated 142 and 144 Salmonella-positive samples, respectively. No significant difference was observed between the two methods for chicken carcasses and pork meat, according to McNemar test at the 5% level.